The party - Hadley, Tessa 1956- (Jonathan Cape, 2024)
"On a winter Saturday night in post-war Bristol, sisters Moira and Evelyn, on the cusp of adulthood, go to an art students' party in a dockside pub; there they meet two men, Paul and Sinden, whose air of worldliness and sophistication both intrigues and repels them. Sinden calls a few days later to invite them over to the grand suburban mansion Paul shares with his brother and sister, and Moira accepts despite Evelyn's misgivings. As the night unfolds in this unfamiliar, glamorous new setting, the sisters learn things about themselves and each other that shock them, and release them into a new phase of their lives."
Keywords: Sisters / Fiction; College students / Fiction; Parties / Fiction; Great Britain / History / George VI, 1936-1952 / Fiction